HAEMATOLOGY AND BLOOD FAT PROFILE OF MUSCOVY DUCK FED WITH DIFFERENT PROTEIN LEVELS SOURCED FROM GOLDEN SNAILS - Kusumadewi, Made Rahayu; Kertawirawan, I Putu Agus; Budiari, Ni Luh Gede (Buletin Veteriner Udayana, 2022)
This research was conducted to see that effect of using golden snail as alternatif fed for Muscovy ducks on different ration level to hematologi profil and blood fat.  64 Muscovy ducks of 8 weeks of age were use in this study use a randomized block design with four treatments and four replications, whereas each replicate consisted of four male Muscovy ducks. The composition of the ration used consisted of corn, rice bran, pollard, coconut meal and golden snail meal. There were four treatments included P0 (control feed), P1 (control feed + 10% golden snail meal), P2 (control feed+20% golden snail meal), P3 (control feed + 30% golden snail meal). The parameters observed were hematological profile including hemoglobin content, erythrocyte count, leukocyte count, and blood hematocrit content and than  blood metabolites including cholesterol, triglycerides, HDL and LDL. The study used a completely randomized design with four treatments and three replicates. The data were subjected to analysis of variance (ANOVA). Based on the results obtained there was no significant difference in erythrocyte levels each treatment, but the hemoglobin level in muscovy duck given 30% golden snail showed significant differences in all treatments. Results of blood metabolites, showed no significant difference in triglyceride levels in all treatments, but the cholesterol content in the ration given 30% golden snail meal (P3) was lower and significantly different from other treatments. In general, giving 30% golden snail meal in the ration shows better results based on the hematological profile